Phytochemical Screening And Tyrosinase Inhibition Activity Of Leaves Cassia siamea L. - Munawarohthus Sholikha; Ainun Wulandari (Universitas Islam Lamongan, 2020)
Cassia siamea L. has been used traditionally as medicine and in previous studies had an IC50 antioxidant activity of 144.12 µg / mL. Cassia siamea L. potential as a medicinal substance is thought to have chemical constituents such as saponins, anthraquinones, alkaloids, flavonoids, tannins, terpenoids and steroids. Indonesia, which is located in a tropical region with high temperatures and ultraviolet (UV) radiation, can cause skin disorders such as hyperpigmentation due to excess melanin synthesis. Tyrosinase enzymes can prevent or inhibit melanin formation. The purpose of this study was to determine the chemical content of Cassia siamea L. leaves extract with various solvents and the inhibitory activity of tyrosinase enzymes. In this study, the leaves of Cassia siamea L. were macerated with methanol as a solvent. The dry methanol extract was fractionated using the liquid-liquid method using aquadest, butanol and chloroform as solvents. The four dried extracts were then phytochemical screening to determine their chemical content. After that, the tyrosinase inhibition test was carried out in vitro with L-Dopa as a substrate using ELISA plate well reader at concentrations of 100, 1000 and 100000 ppm with three repetitions (triplo). The methanol extract had percent inhibition of 19.993 ± 1.125%, 28.984 ± 0.624%, 57.164 ± 0.623%, respectively; butanol fraction 25.914 ± 0.541%, 32.566 ± 0.767%, 52.120 ± 1.616%; chloroform fraction 19.920 ± 0.730%, 26.425 ± 0.937%, 62.865 ± 0.167% and aquadest fraction 23.830 ± 0.879%, 30.885 ± 0.778%, 67.471 ± 0.352%. Kojic acid had tyrosinase activity and acts more active than the other extract and fraction with 91.155±0.228% at 500 ppm. The butanol fraction had the highest percent inhibition at 100 and 1000 ppm which was thought to be due to the presence of alkaloids, tannins, flavonoids, steroids and terpenoids from the results of the phytochemical screening test.